THE DYNAMICS OF WOMEN'S PSYCHOLOGICAL WELL-BEING IN TAARUF MARRIAGES - Qori Setyo Ningrat; Diana Rahmasari; Hermien Laksmiwati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to describe the psychological well-being of women who marry through the taaruf process and the factors that influence it. This study focuses on four main themes of psychological well-being: self-acceptance, positive relationships with others, environmental mastery, and life goals, using a qualitative approach. The four participants were selected through purposive sampling. The results show that the psychological well-being of women in taaruf marriages is strongly influenced by positive self-acceptance, the ability to establish good relationships with partners and families, and the ability to manage stress and adjustment. This study is expected to provide a deeper understanding of the psychological challenges of taaruf marriages to improve the psychological well-being of women in taaruf marriages.